Ilustraciones de cuentos costumbristas ignotos de la Provincia de El Oro - Villamar Martínez, Washington Darío (Machala : Universidad Técnica de Machala, 2022)
The foundation of the present work, Illustrations of traditionals tales unknown of the El Oro province, originates in function at the cultural interest what is expressed trough of the different possibilities and means of artistic production, and what for part of the fusion between literature and the illustration practice, an investigative process is proposed in the compilation of stories, the which are conceived through the graphic representation in one list of fourteen illustrations tales autochthonous of our province. Over time, the tradition of telling stories, tales, legends or anecdotes of costumbrista character typical of our identity towards the youngest loses its essence as such, given that new trends and thoughts influence the lack of interest in discovering small fragments of the culture and history forged by our grandparents long ago. Part of the essential idea in the investigation is established to the action of rescued, keep record, spread and encourage the attention and appreciation towards that part of the intangible culture what constitutes us, properly the various oral expressions what characterize our identity in the various Orense communities Throughout our lives we have been listening witnesses of various stories that at the time were shared by our elders, we know that within our province there are peasant. communities in the rural parishes of the different cantons and that therefore our cultural essence arises from these places, where technological development, the impact of new trends or lifestyles do not completely displace or have still displaced that costumbrista identity, and it is here where the tradition of telling stories or tales is born and maintained in a very passive way. of a fantastic or realistic character, events that arose in past times, and that over time became the autochthonous identity of these localities, which are an essential part and explain why many times popular denominations arise towards the different sectors, spaces, places, objects or people, that in a superficial way we could hear and know, but not knowing the main reason for being. On the other hand, illustration serves as a graphic resource which provides embellishment to the work, mainly serves to create full interest and simplify the content and assessment of the stories represented, as a method of learning towards the culture that makes us in our Province. We have a study that covers the history of illustration, from its origins to the present, its different methods of conception, its use and complementation in the improvement of society. Then contextualized historical content of our national environment is also evidenced, how this activity arises, when it is recognized and how it has been maintained until now. It can be argued that as a primary objective in the development of the artistic proposal, it is established to achieve the aesthetic effect that only an illustration can generate in the accompaniment of a narration, capturing the taste of the readers, whether they are children, young or old, art manages to achieve that committed regardless of age.
La fundamentación del presente trabajo, Ilustraciones de cuentos costumbristas ignotos de la provincia de El Oro, se origina en función al interés cultural que es expresado a través de las diferentes posibilidades y medios de producción artística, y que por parte de la fusión entre la literatura y la práctica de la ilustración, se plantea un proceso investigativo en la recopilación de relatos, los cuales son concebidos a través de la representación gráfica en una lista de catorce cuentos ilustrados autóctonos de nuestra provincia. Al paso del tiempo, la tradición de relatar historias, cuentos, leyendas o anécdotas de carácter costumbrista propias de nuestra identidad hacia los más jóvenes pierde su esencia como tal, dado que las nuevas tendencias y pensamientos influyen en la falta de interés por descubrir pequeños fragmentos de la cultura e historia forjada por nuestros abuelos tiempos atrás. Como idea esencial en la investigación se encuentra establecida la acción de rescatar, documentar, difundir e incentivar la atención y valoración hacia aquella parte de la cultura intangible que nos constituye, propiamente en las diversas expresiones orales que caracterizan nuestra identidad en las variadas comunidades orenses. A lo largo de nuestras vidas hemos sido testigos oyentes de diversos relatos que en su momento nos eran compartidos por nuestros mayores, conocemos que dentro de nuestra provincia existen comunidades campesinas en las parroquias rurales de los diferentes cantones y que por ende nuestra esencia cultural surge desde estos sitios, donde el desarrollo tecnológico, el impacto de nuevas tendencias o estilos de vida no desplazan o han desplazado todavía aquella identidad costumbrista de manera total, y es aquí donde surge y se mantiene de manera muy pasiva la tradición de contar historias o cuentos sea de carácter fantástico o realista, acontecimientos que se suscitaron en tiempos pasados, y que al paso del tiempo se volvieron identidad autóctona de estas localidades, las cuales son parte esencial y explican por qué muchas de las veces surgen denominaciones populares hacia los diferentes sectores, espacios, lugares, objetos o personas, que de manera superficial podríamos escuchar y conocer, pero no saber la razón principal de ser. Por otro lado, la ilustración nos sirve como un recurso grafico el cual brinda embellecimiento a la obra, principalmente sirve para crear un interés pleno y simplificar el contenido y la valoración de los cuentos representados, como método de aprendizaje hacia la cultura que nos conforma en nuestra provincia. Disponemos de un estudio que abarca la historia de la ilustración, desde sus orígenes hasta la actualidad, sus diferentes métodos de concepción, su uso y complementación en la mejoría para la sociedad. Luego también se evidencia contenido histórico contextualizado de nuestro medio nacional, como surge dicha actividad, en qué momento es reconocida y como se ha mantenido hasta ahora. Cabe argumentar que como objetivo primordial en el desarrollo de la propuesta artística se establece lograr el efecto estético que solo una ilustración puede generar en el acompañamiento de una narración, acaparando el gusto por los lectores sean estos niños, jóvenes o mayores, el arte logra conseguir aquel cometido indiferentemente a las edades.
Keywords: ILUSTRACION; CULTURA; REPRESENTACION; ARTE